2022
DOI: 10.3389/fimmu.2022.892331
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of serological response to anti-SARS-CoV-2 mRNA vaccination in hematological patients

Abstract: IntroductionIn immunocompromised patients, SARS-CoV-2 mRNA vaccine has been used in Italy from the beginning of the vaccination campaign, but several studies have shown that the serological response of onco-hematological patients was reduced compared to healthy subjects, due to the state of immunosuppression because of both underlying disease and administered therapy.MethodsWe evaluated the association of anti-SARS-CoV-2 spike IgG titers in 215 hematological patients with clinical and demographic variables to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 24 publications
(27 reference statements)
0
1
0
Order By: Relevance
“…In the majority of investigated participants in the study by Petzer and colleagues, 30 a humoral response to the vaccines was measured. However, in studies by Pascale and colleagues 31 and Haggenburg and colleagues, 32 a great diversity of SARS-CoV-2 antibody responses in accordance with different types of hematological diseases and therapies was observed. Another study showed that hematological patients, especially those diagnosed with multiple myeloma, were at higher risk for a breakthrough infection after being partially or fully vaccinated with mRNA COVID-19 vaccines compared with cancer patients with a solid tumor.…”
Section: Introductionmentioning
confidence: 99%
“…In the majority of investigated participants in the study by Petzer and colleagues, 30 a humoral response to the vaccines was measured. However, in studies by Pascale and colleagues 31 and Haggenburg and colleagues, 32 a great diversity of SARS-CoV-2 antibody responses in accordance with different types of hematological diseases and therapies was observed. Another study showed that hematological patients, especially those diagnosed with multiple myeloma, were at higher risk for a breakthrough infection after being partially or fully vaccinated with mRNA COVID-19 vaccines compared with cancer patients with a solid tumor.…”
Section: Introductionmentioning
confidence: 99%